Break Time Bully-Victim: Exploring What Makes an Individual Commit Bullying and How It Affects Him - Yonas Putra (Institute of Research and Community Outreach - Petra Christian University, 2019)
When we talk about bullying, the focus is usually about the victim and exploring how will the victim survive from that and how he overcomes that problem. However, the creative work that I make is different from the usual story. In my creative work, the point of view of story will be from a teenager who commits the bullying. In my story, it will talk about why my main character commits the bullying until he killed his classmate. He does not realize that he is manipulated by his friend and also his upper classmate called Max. The story will reveal why Ronald can become a bully in senior high. The main theme that is used in this work is how guilt changes a person’s personality and way of thinking. His desire to get acknowledgement when he enters senior high and does not want to repeat the same experience in junior high makes him become a bully in senior high. The story is presented through the genre of psychology and focuses on bullying and story behind it. Keywords: bullying, bully-victim, frenemy, Difficult home life, crime.